EUS-FNA for pancreatic cyst lesion, today and tomorrow in the kingdom of Thailand - Kongkam P. (2014)
Unlike endoscopic retrograde cholangiopancreatography (ERCP) service, endoscopic ultrasonography (EUS) service in Thailand is at its elementary state. Currently, there are only 11 hospitals in Thailand carrying out EUS whereas there are more than 50 hospitals carrying out ERCP. This is a multicenter questionnaire survey that obtained information on EUS practice for pancreatic cysts.Of those 11 hospitals, only three hospitals provided enough number of patients with pancreatic cysts undergoing EUS. There were many differences in endosonographers opinions regarding specific information in the pancreatic cyst. In addition, the threshold to carry out and not to carry out fine needle aspiration are varies. © 2011 The Authors Digestive Endoscopy © 2011 Japan Gastroenterological Endoscopy Society.